PENERAPAN METODE FUN LEARNING PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI TERHADAP AKTIVITAS BELAJAR PESERTA DIDIK DI SD IT BAITUL JANNAH BANDAR LAMPUNG - Maylia Khairunnisa Baher; Zulhanan; Guntur Cahaya Kusuma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of the fun learning method in Islamic Religious Education and Character (PAIBP) learning, the dynamics of students' learning activities, and the supporting and inhibiting factors in its implementation at SD IT Baitul Jannah Bandar Lampung. This research uses a qualitative approach with a case study design. Data collection techniques were carried out through observation, interviews, and documentation. The research informants consisted of PAIBP teachers and sixth-grade students. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results show that the implementation of the fun learning method in PAIBP learning is carried out through three main stages: planning, implementation, and evaluation of learning. During the implementation stage, teachers apply various interactive learning activities such as educational games, storytelling, singing, humor, and guessing games to create a joyful learning environment. The implementation of this method encourages the emergence of various student learning activities, including visual activities, oral activities, listening activities, motor activities, and writing activities. In addition, the implementation of fun learning is supported by teacher creativity, student enthusiasm, and the availability of learning facilities. However, several challenges were also found, such as limited learning time and differences in student characteristics. Overall, the fun learning method contributes positively to creating a more interactive and engaging learning process in PAIBP classes.